How they Rule the World: The 22 Secret Strategies of Global Power - Pedro Baños (Ebury Press, 2019)
Wherever you turn - Europe, Russia, China, Korea, Syria, the Middle East - we are living in a time of global geopolitical power plays. Once an insider to this closed world, Pedro Banos reveals that however it might be smoothed over by the PR of political diplomacy, the world of geopolitics is one of war and conflict by strategic means, where countries have sought dominion and power over their rivals since the dawn of time. Banos presents this high-stakes game as a series of 22 universal rules on how to act and exert influence in the international sphere. Each principle is contextualised in both classical and modern history, from Bismarck to Kissinger, but also related to the current world of Trump, Putin and Xi Jinping. With titles like 'Kicking Away the Ladder', 'The Tower of Champagne Glasses', 'The Madman', and 'The Mule and the Saddlebags', How They Rule the World is a practical set of rules for engagement that can be enjoyed by anyone. Written with the philosophic, aphoristic timelessness of a von Bulow, Sun Tzu or Machiavelli, Banos has created an utterly gripping manual on the secrets of how strategic power really works.